2010
DOI: 10.1093/chromsci/48.7.589
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Determination of Piracetam and its Four Impurities by RP-HPLC with UV Detection

Abstract: A simple and rapid high-performance liquid chromatographic method for the separation and determination of piracetam and its four impurities, 2-oxopyrrolidin-1-yl)acetic acid, pyrrolidin-2-one, methyl (2-oxopyrrolidin-1-yl)acetate, and ethyl (2-oxopyrrolidin-1-yl)acetate, was developed. The separation was achieved on a reversed-phase C(18) Nucleosil column (25 cm x 0.46 cm, 10 microm). The mobile phase is composed of an aqueous solution containing 0.2 g/L of triethyl amine-acetonitrile (85:15, v/v). The pH of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Figure 2. Structure of fexofenadine hydrochride During literature survey it was found that, various HPLC methods have been estimated for the determination of montelukast sodium [4][5][6][7] and fexofenadine hydrochloride [8][9][10][11] in combination with other drugs but no RP-HPLC method has been determined till date. Hence an attempt has been made to develop and validate a simple, economic, rapid and accurate method.…”
Section: -[2-(1-hydroxy-1-methylethyl) Phenyl] Propyl -Sulfanylmethymentioning
confidence: 99%
“…Figure 2. Structure of fexofenadine hydrochride During literature survey it was found that, various HPLC methods have been estimated for the determination of montelukast sodium [4][5][6][7] and fexofenadine hydrochloride [8][9][10][11] in combination with other drugs but no RP-HPLC method has been determined till date. Hence an attempt has been made to develop and validate a simple, economic, rapid and accurate method.…”
Section: -[2-(1-hydroxy-1-methylethyl) Phenyl] Propyl -Sulfanylmethymentioning
confidence: 99%
“…It is used in the treatment of upper respiratory tract diseases [5]. Some analytical methods have been reported for the determination of LCD either alone [6][7][8][9] or in combination with other drugs using high performance liquid chromatography [10][11][12][13][14][15], thin layer chromatography [16] and UV spectrophotometry [17][18][19][20][21][22]. As well, a number of methods have been reported for the individual determination of ABH [23][24][25][26][27], and in combination with other drugs in pharmaceutical dosage form by high performance liquid chromatography [28][29][30][31][32][33], liquid chromatography-mass spectroscopy/mass spectroscopy [34], thin layer chromatography [35], UV spectrophotometry [36,37] and high performance thin layer chromatography [38,39].…”
Section: Introductionmentioning
confidence: 99%
“…Our Research Group already has done some work in the field of analytical method development for antihistamine drugs [30][31][32][33][34][35] .…”
Section: Introductionmentioning
confidence: 99%